Meaningful materials? Bone artefacts and symbolism in the Early Bronze Age Aegean - Isaakidou, V (Wiley, 2017)
The symbolically laden use of materials is well documented ethnographically but hard to demonstrate archaeologically, especially for animal bones and teeth, use of which in post-Neolithic contexts is commonly considered expedient. Early Bronze Age southern Aegean mortuary assemblages have yielded three distinctive classes of bone artefact. Comparison with contemporary unworked bone assemblages and contextually or formally related objects in other materials reveals complex cultural associations, the symbolic meaning of which is explored through heuristic use of ethnographic analogues. It is concluded that alternative value systems operated alongside those structured around exoticism and technological sophistication, usually deployed to understand EBA southern Aegean cultures.